Napoleon - Roberts, Andrew (New York Penguin, 2015)
An award-winning historian, Roberts traveled to fifty-three of Napoleon$1 (Bs sixty battle sites, discovered crucial new documents in archives, and even made the long trip by boat to St. Helena.s
Keywords: Biography